Shadow puppetry therapy enhances dementia-related cognitive function and interpersonal relationship - Shu-Yuan Chao; Hsiao-Mei Chen; Bei-Yi Su (Experimental Gerontology)
Background: With the growing demand for dementia care, non-pharmacological interventions, such as creative arts therapies, have been proven effective in stabilizing cognitive function. Shadow Puppetry Therapy (SPT), which integrates visual, auditory, and kinesthetic elements, offers a promising care option for individuals with dementia. Objective: This study evaluated the effectiveness of SPT on cognitive function, self-esteem, and interpersonal relationships among older adults with mild dementia. Methods: We adopted a quasi-experimental design and recruited 33 older adults with mild dementia from two dementia care centers. Older adults with mild dementia were randomly assigned to an experimental group (n = 15) and a control group (n = 18). The experimental group participated in a 16-week SPT program, and the control group engaged in regular activities, such as physical exercises, painting, cooking, music, and handicraft projects. Assessments included the short portable mental status questionnaire (SPMSQ), the Rosenberg self-esteem scale (RSES), and the interpersonal relationship scale, with evaluations conducted before and after the intervention. Results: The intervention significantly improved cognitive function, self-esteem, and interpersonal relationships in the experimental group. SPMSQ scores decreased, indicating enhanced cognitive function (p = .001), while self-esteem and interpersonal relationship scores showed significant improvements (p = .001). No significant changes were observed in the control group. Conclusion: SPT is an effective non-pharmacological intervention for enhancing cognitive function, self-esteem, and interpersonal relationships in older adults with mild dementia. The findings support the integration of creative arts therapies into dementia care.